Rasio Keuangan yang Paling Baik sebagai Prediktor Risiko Sistematik Suatu Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Jakarta - Meythi . (Jurnal Akuntansi, 2007)
This research is aimed to determine the best financial ratios in predicting systematic risk. There are 12 financial ratios [current ratio (CR), quick ratio (QR), debt ratio (DR), equity to total asset (ETA), equity to total liabilities (ETL), equity to fixed asset (EFA), profit margin (PM), return on asset (ROA), return on equity (ROE), fixed assets turnover (FAT), total asset turnover (TAT), and correction beta (BK) ] categorized into four factors(liquidity/solvability factor, profitability factor, activity factor, and systematic risk factor) in predicting systematic risk. Data of research are collected from manufacturing firms which listed on the Jakarta Stock Exchange during 2000-2003. Tests were undertaken using factor analysis to determine the best financial ratios in predicting systematic risk. The results shows that return on asset (ROA) is the best financial ratio in predicting systematic risk.Keywords: financial ratios, systematic risk, and factor analysis.